1986
DOI: 10.1177/002221948601900107
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cognitive Strategy Training on Verbal Math Problem Solving Performance of Learning Disabled Adolescents

Abstract: This study investigated the effect of an eight-step cognitive strategy on verbal math problem solving performance of six learning disabled adolescents. The cognitive strategy was designed to enable students to read, understand, carry out, and check verbal math problems that are encountered in the general math curriculum at the secondary level. Conditions of the multiple baseline desing included baseline, treatment, generalization, maintenance, and retraining. During treatment, students received strategy acquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 43 publications
2
73
0
1
Order By: Relevance
“…Word problem-solving instruction in mathematics for students with mild disabilities has shifted from an emphasis on instruction in key words and computational skills to a focus on instruction in problem comprehension (Englert et al, 1987) and cognitive and metacognitive processing (e.g., Montague, 1992Montague, , 1995. It is an instruction that emphasizes conceptual understanding (Hiebert & Carpenter, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Word problem-solving instruction in mathematics for students with mild disabilities has shifted from an emphasis on instruction in key words and computational skills to a focus on instruction in problem comprehension (Englert et al, 1987) and cognitive and metacognitive processing (e.g., Montague, 1992Montague, , 1995. It is an instruction that emphasizes conceptual understanding (Hiebert & Carpenter, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In their research synthesis, Jitendra and Xin found only 14 published studies conducted in the last I0 years that involved the use of systematic strategies for mathematics word problem solving with students with identified disabilities or with students who were receiving remedial mathematics instruction. Most of the approaches reported in the literature have relied on information processing or cognitive models of mathematical problem solving (Case, Harris, & Graham, 1992;Hutchinson, 1993;Jitendra & Hoff, 1996;Montague, 1992;Montague, Applegate, & Marquard, 1993;Montague & Bos, 1986;Zawaiza & Gerber, 1993). These models emphasize problem representation (i.e., translating a problem from words into a meaningful representation) and problem solution (i.e., both solution planning and execution of mathematical operations).…”
mentioning
confidence: 99%
“…The idiographic detail of schemata acquisition this present study provides through a continuous measure of problem-solving ability illustrates the potential that within-subject methodology has for research in problem-solving skills training (Montague & Bos, 1986;Church, 1991;Montague, 1992). However, two limitations to the present study must be acknowledged.…”
Section: Discussionmentioning
confidence: 83%
“…During the intervention, the strategy group received explicit strategy plus traditional instruction in whole-class format for four classes (45 min each) a week. Strategy instruction composed of two training phases called strategy acquisition and strategy application as used in Montague and Bos (1986). Strategy acquisiton is the phase where students learn the particular learning strategies (in this study, questioning, summarizing, and graphic organizers).…”
Section: Methodsmentioning
confidence: 99%